The complement cascade at the Utah microelectrode-tissue interface. (January 2021) - Bennett, Cassie; Álvarez-Ciara, Anabel; Franklin, Melissa; Dietrich, W. Dalton; Prasad, Abhishek
Abstract: Devices implanted within the central nervous system (CNS) are subjected to tissue reactivity due to the lack of biocompatibility between implanted material and the cells' microenvironment. Studies have attributed blood-brain barrier disruption, inflammation, and oxidative stress as main contributing factors that lead to electrode recording failure. The complement cascade is a part of the innate immunity that focuses on recognizing and targeting foreign objects; however, its role in the context of neural implants is substantially unknown. In this study, we implanted a non-functional 4x4 Utah microelectrode array (UEA) into the somatosensory cortex and studied the complement cascade via combined gene and immunohistochemistry quantification at acute (48-h), sub-acute (1-week), and early chronic (4-weeks) time points. The results of this study demonstrate the activation and continuation of the complement cascade at the electrode-tissue interface, illustrating the therapeutic potential of modulating the foreign body response via the complement cascade.